Antimicrobial Sensitivity Pattern of Urine Culture Isolate in a tertiary Care Hospital - Jais Kumar Karmani, Armughan Ahmad, Muddasar Iqbal, Naveed Arshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To observe sensitivity patterns of urinary tract infections and the micro-organisms causing them in patients presenting with urinary tract symptoms. Methodology: A sample of 206 patients presenting with complaints of lower urinary tract symptoms and ranging between the age group of 20 to 85 years was included in the study. This was a retrospective study that was carried out in the departments of nephrology at Dr. Akbar Niazi Teaching Hospital (ANTH), Islamabad, from January 2019 to January 2020. Urine samples were collected in sterile containers and processed. Culture and sensitivity analysis based on investigative testing was carried out. CLED medium was used to sub-culture the colonies to get pure growth of the micro-organisms. The Kirby-Bauer disc diffusion process was employed to find the susceptibility of antibiotic in isolated colonies.The bacterial growth was measured after incubation in compliance with the clinical and laboratory standards institute (CLSI) guidelines. Results: Escherichia Coli was detected in 77 patients (84.6%) among the 91 positive urine cultures; Klebsiella species was found in 7 patients (7.7%); Enterococcus species was present in 6 patients (6.6%) and Pseudomonas was found in 1 patient (1.1%). Maximum efficacy was observed with Imipenem and Fosfomycin (80.5%) followed by Nitrofurantoin (75.3%). All cultures were resistant to Amoxicillin. Conclusion: Our study shows, Imipenem and Fosfomycin to be the most effective drugs in treatment of UTIs. E coli remains the most common causative organism in this disease and the increase in drug resistance by uropathogens are of significant concern.Communities may benefit from implementation of health education to prevent antibiotic sharing and similar drug abuse. Keyword: Anti-infective agents; Culture; Microbial sensitivity tests; Urine; Uropathogens; Urinary tract infections.